Exploiting somatic oncogenic driver alterations in a patient with Li-Fraumeni syndrome– paving the path towards precision medicine: a case report - Carolin Seeling; Sonja Dahlum; Ralf Marienfeld; Vera Jan; Brigitte Rack; Uwe Gerstenmaier; Ambros J. Beer; Regine Mayer-Steinacker; Wolfgang Thaiss; Thomas F. E. Barth; Thomas Seufferlein; Nadine T. Gaisa; et al. (Journal of Cancer Research and Clinical Oncology, 2025)
Abstract Background Li-Fraumeni syndrome (LFS) is an autosomal dominant tumor predisposition syndrome characterized by a high familial incidence of various malignancies. It results from pathogenic/likely pathogenic heterozygous constitutional variants of the TP53 gene. Due to impaired DNA damage repair, conventional cytotoxic therapies or radiotherapy should be avoided whenever feasible to mitigate the high incidence of treatment-related secondary malignancies in these patients. However, there is limited evidence supporting the effectiveness of targeted therapy approaches in LFS patients. Case presentation We present the case of a woman with breast cancer and subsequent osteosarcoma, both treated with surgery and chemotherapy. Constitutional genetic germline testing identified a pathogenic TP53 variant in line with the clinical features of Li-Fraumeni syndrome. Subsequent molecular analysis of the osteosarcoma tissue revealed homozygous loss of the CDKN2A gene locus, warranting treatment with CDK4/6 inhibitor palbociclib. Palbociclib therapy was discontinued after one year with no evidence of disease. One year later, ovarian cancer was diagnosed, with molecular analysis indicating interstitial heterozygous loss of the BRCA2 gene locus, providing a rationale for targeted therapy with the PARP inhibitor olaparib. Conclusions In the era of accessible and comprehensive genetic and phenotypic tumor profiling, this case study of a patient with Li-Fraumeni syndrome underscores the success of precision oncology in harnessing additional somatic oncogenic driver alterations. Furthermore, it emphasizes the indispensable role of an interdisciplinary molecular tumor board, enhancing the awareness of molecular profiling and targeted therapies in patients with rare cancer susceptibility disorders.